2022
DOI: 10.1002/marc.202100687
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Ionic Conductivity and Microstructure in Polyelectrolyte Hydrogels for Bioelectronic Devices

Abstract: Hydrogels have become the material of choice in bioelectronic devices because their high-water content leads to efficient ion transport and a conformal interface with biological tissue. While the morphology of hydrogels has been thoroughly studied, systematical studies on their ionic conductivity are less common. Here, an easy-to-implement strategy is presented to characterize the ionic conductivity of a series of polyelectrolyte hydrogels with different amounts of monomer and crosslinker and correlate their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Prior to this transition, ≲10 mM KBr, it could then be expected to be an ideal condition for PCPDTBT-SO 3 – K + as a structural scaffold and dual ion–electron conductor. A more swollen homogeneous network of π-conjugated chains, physically cross-linked by ionic clusters and with mobile small ions, could be expected to be ideal in terms of maximized elastic modulus, electronic mobility, and ion conductivity, due to a percolated conjugated polymer network connecting the electrodes and free volume in the bulk for hydrated ion conduction. , Interestingly, since these structural transitions occur at millimolar salt concentrations approaching physiological conditions, there is an opportunity for ionic sensing or actuation in bioelectronic applications. This emphasizes that control over the assembly of CPEs in aqueous solutions with added salt and biologically relevant buffers is critical for realizing modular, soft, conductive matrices. , …”
Section: Resultsmentioning
confidence: 99%
“…Prior to this transition, ≲10 mM KBr, it could then be expected to be an ideal condition for PCPDTBT-SO 3 – K + as a structural scaffold and dual ion–electron conductor. A more swollen homogeneous network of π-conjugated chains, physically cross-linked by ionic clusters and with mobile small ions, could be expected to be ideal in terms of maximized elastic modulus, electronic mobility, and ion conductivity, due to a percolated conjugated polymer network connecting the electrodes and free volume in the bulk for hydrated ion conduction. , Interestingly, since these structural transitions occur at millimolar salt concentrations approaching physiological conditions, there is an opportunity for ionic sensing or actuation in bioelectronic applications. This emphasizes that control over the assembly of CPEs in aqueous solutions with added salt and biologically relevant buffers is critical for realizing modular, soft, conductive matrices. , …”
Section: Resultsmentioning
confidence: 99%
“…We also consider the IEM as pre‐loaded with the ion we are trying to deliver via soaking, allowing the hydrogel IEM to reach equilibrium. [ 18 ] From this representation, it is clear that a smaller V polarization will result in a larger I for the same V pump . Therefore, it is important to consider the contribution to V polarization of different WEs when developing bioelectronic ion pumps, as the choice of electrode material plays a significant role in the resulting current and efficiency of cargo delivery.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10a,23 ] The IEM is selectively permeable to the desired cargo (Figure 1b). [ 24 ] For this work, we use H + as the cargo, 2‐acrylamido‐2‐methylpropane sulfonic acid (AMPSA)/poly (ethylene glycol) diacrylate (PEGDA) (AMPSA/PEGDA) hydrogel [ 18 ] as the IEM, Ag/AgCl as the RE/CE, and Ag, Pt, or PdH x as the WE. Since we want directional ion migration, DC is required to drive the ion pump and we do not consider AC conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the mechanical properties, especially stretchability, and the conductivity of the hydrogel-based WFEs are weakened, leading to inaccurate or even failed measurements of physiological signals. [21][22][23] Therefore, visualizing the dehydration of hydrogels is of great importance for the user to evaluate the sensing performance and to rehydrate or replace the assembled hydrogel electronics in a timely manner. However, research on this topic has rarely been reported.…”
mentioning
confidence: 99%